A retrospective study of the correlation between herpes zoster neuralgia and the serum neuron-specific enolase level in the largest dermatological hospital in Zhejiang province, China - Zhong, Changyang; Lin, Ding; Liu, Yuan; Wu, Chunli (Frontiers in Immunology, 2022)
We studied the changes and clinical significance of the serum neuron-specific enolase (NSE) level in peripheral blood of patients with post-herpetic neuralgia (PHN). Material and Methods: Patients with PHN were divided into a mild PHN group and a severe PHN group according to their scores on a 100-point Likert scale representing the degree of neuralgia. NSE levels in neuralgia patients and healthy volunteers were then compared by t-test. Receiver operating characteristic curve analysis was performed to evaluate the diagnostic efficiency of NSE for PHN. The correlation between NSE level and Likert scale score after treatment was analyzed. Results:NSE levels in PHN patients were higher than those in the healthy volunteers. Patients in the severe PHN group had higher NSE levels than those in the mild PHN group. NSE level at admission was associated with the Likert scale score recorded on the 14th day of treatment (136.1 ± 32.81 vs. 87.53 ± 16.23 pg/mL) (P < 0.05). The ROC curve of NSE levels for PHN is show that the area was 0.8713 (95% confidence interval, 0.7861¬–0.9564; p < 0.0001).Conclusions:There was a correlation between NSE and PHN, in that the NSE level correlated with the short-term prognosis of patients with PHN.